TO QUESTION ABOUT RARE PATHOLOGY OF VESSELS OF MAXILLО-FACIAL AREA - Skikevych, M.G.; Avetikov, D.S.; Соколов, В.М. (World of Medicine and Biology, 2012)
Arterial and venous communications, developmental anomalies of veins and arteries of maxillofacial area concern to congenital developmental anomalies of peripheral vessels - malformations. The problem of treatment of patients with developmental anomalies of vessels is one of the most difficult sections of clinical medicine. The analysis of case records of maxillofacial patients with malformations for the period 2001 till 2011 is carried out with leading information. For six years (with 2001 on 2006) in branch it is made operations of 5315 patients, and the next five years (2007-2011)-5064, that testifies to activation of operative activity, and the percent (interest) of vascular malformations and anomalies has decreased. Rendering of high specialization the help at the given pathology is expedient on the basis of a versatile surgical hospital with good diagnostic base and with use of a principle of the multidisciplinary approach. Precisely planned algorithm of examination, supervision and care in many respects defines a favorable outcome of treatment even at heavy urgent conditions in maxillofacial surgery.
Keywords: angiodysplasia; malformations; an aneurism; hemangioma of the head and neck